Descriptive analysis of Overall Equipment Effectiveness (OEE) in various industry - S T Risyahadi; F Apriliani; S Irawan (Institut Teknologi Sepuluh Nopember, 2018)
Industry has to increase their competitiveness in order to make high profits and customer satisfaction. One of its efforts is the application of TPM (Total Productive Maintenance) in any machine production to maximize effectiveness of machine. The OEE (Overall Equipment Effectiveness) is used as an indicator effectiveness of the machine that important to be measured. This research aims to know to scatter value OEE in various type industries, The data in this research were obtained from collecting students' final task reports on Industrial Management Program Diploma IPB who has done internship program in the industry with the topic Total Productive Maintenance. The results indicate that average OEE value in FMCG, Textile, Chemical Industry and Manufacture Components are more than 60% but lower than 85%, so that is still below the value of the world class industry. Furthermore, availability score has reached world class standard, while performance and quality is still below world class.